A novel chalcone derivative S17 induces apoptosis through ROS dependent DR5 up-regulation in gastric cancer cells - Zhang, Saiyang; Li, Tingyu; Zhang, Li; Wang, Xiangyu; Dong, Hangqi; Li, Lili; Fu, Dongjun; Li, Yongchun; Zi, Xiaolin; Liu, Hong-Min; Zhang, Yanbing; Xu, Hongde; et al. (Scientific reports, 2017)
A new series of etherification chalcone derivatives were designed and synthesized through Willimison etherification and Claisen-Schmidt condensation. Among them, compound 2-c which was given chemical name of S17 , has been successfully screened out as the most potent one on gastric cancer cell line(MGC803) through the investigation for their effects against the growth of five cancer cell lines (EC109, HepG2, MCF7, MGC803, SKNSH). S17 exhibited strong anti-proliferative activity on other two gastric cancer cells (HGC27 and SGC7901), but less cytotoxicity to non-malignant gastric epithelial cells GES1. S17 potently killed gastric cancer cells with causing modulation of Bcl-2 family proteins and activation of caspase 9/3 cascade. S17 also up-regulated DR5 expression and DR5 knockdown partially reversed S17 -induced apoptosis, caspase activation and MMP decrease. S17 robustly induced generation of ROS with Keap/Nrf2 pathway activated and the application of ROS scavenger N-acetyl cysteine (NAC) completely blocked these effects by S17 in MGC803 cells. Intraperitoneal administration of S17 significantly inhibited the growth of MGC803 cells in vivo in a xenograft mouse model without observed toxicity. These results indicated that S17 is a leadbrominated chalcone derivate and deserves further investigation for prevention and treatment of gastric cancer.